PENGARUH E-PAYMENT SERVICES DAN E-COMMERCE SERVICES TERHADAP KINERJA UMKM YANG DIMEDIASI OLEH DIGITALIZATION KNOWLEDGE “STUDI KASUS PADA UMKM FOOD AND BEVERAGE DI DAERAH ISTIMEWA YOGYAKARTA” - Yudas Tadius Andi Candra; Azfa Mutiara Ahmad Pabulo (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2024)
The advancement of information technology and the COVID-19 pandemic has prompted Micro, Small, and Medium Enterprises (MSME) to shift towards e-payment and e-commerce services. This research aims to investigate the influence of E-Payment and E-Commerce services on the performance of MSME in the food and beverage sector in the Special Region of Yogyakarta, with digital knowledge as a mediator. The study employs the quantitative analysis method of Partial Least Square (PLS) involving 255 MSME. The results reveal that E-Payment services do not significantly impact MSME performance, while E-Commerce services have a significantly positive effect. Digital knowledge mediates the positive relationship between E-Payment and E-Commerce services and MSME performance. The implication is that MSME needs to consider more integrated strategies in adopting technology in this digital era to enhance their performance.